Comparison between primary method analysis and nir analysis in determination of nutrient content in tempeh - Nur Hazwani, Rosli (2010)
The objective of this study is to compare the analysis of nutrient content in tempeh by using primary method analysis and Near Infrared(NIR)analysis and the nutrient content utilized from using different types of packaging also been compared.The nutrient content that is analyzed is protein content,fat content,fiber and also ash content.Random samples from Kuantan area were taken to be analyzed with primary method analysis and NIR analysis.Tempeh samples with different types of packaging also been analyzed on the nutrient content.From here the nutrient utilized in each types of packaging were compared.From the results,it shows that there are similarities on the analysis between conventional method and NIR analysis.The percentage differences are about 2 to 20% difference depending on the errors during the analysis.The results also show that the plastic packaging utilizes lower protein content than paper packaging but preserved longer by using plastic packaging.